Fusion of principal component of multispectral bands with PAN band using HIS and wavelet transform - Chitwong, S.; Cheevasuvit, F.; Homthong, J. (My University, 2002)
Since RGB images derived from multispectral (TM) images will lose some information, in this paper we present the method to solve such problem by using principal component analysis (PCA) which transforms TM images into the principal component images (PCs), while the high resolution PAN data is decomposed by wavelet transform. Thus, RGB images are assigned by the first three principal component images which normally have approximately 95% of the information in the original images. The intensity image from RGB to HIS transformation is replaced by the lower frequency coefficient of wavelet transform of PAN data corresponding to multispectral images. HIS to RGB transformation is then applied. The fused RGB image using our method can obtain more details.
Keywords: Data fusion; Hue-Intensity-Saturation transform; Principal Component Analysis; Wavelet transform